Translation as a Learning Experience: Insights from Cognitive Psychology and Psycho-Pedagogy - MADOUI, Saoussen (Journal of Human Sciences, 2019)
Translation teaching is, often, envisioned solely as a problem of content or approach translating a strong desire to give a new breath to the discipline and help it gain its autonomy in order to be taught for its own sake and to be easily distinguished from a traditional language class. In the midst of this educational turmoil, consideration of the learning enterprise as such seems to be ignored. Future translators are learners who need to continue learn for the rest of their life. They need to develop their independence in thinking and decision. To help students in this respect, a teacher needs to gain insights about psycho-pedagogy and cognitive psychology to understand what learning is and how best it can be promoted and developed. This work is a discussion of the different threads of learning and how they can be manipulated in the service of the future autonomous translators.